Pelatihan Critical Literacy Guna Meningkatkan Kualitas Pembelajaran Bahasa Inggris tingkat Sekolah Dasar - Sari, Nadia Tiara Antik; Wulan, Neneng Sri; Nurmahanani, Indah; Nurrohmat, Titin; Althamiranda, Alfira; Anugrah, Yuwan Fijar (Muttaqien Publishing Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR. KH.EZ. Muttaqien Purwakarta, 2025)
Critical Literacy is an educational approach that encourages individuals, especially children, to analyze and question texts and their contexts. This method is vital for helping children critically assess information and avoid misinformation in today’s digital age. This community service project aims to raise awareness about the importance of critical literacy among elementary school students through an interactive webinar involving teachers and students. Preliminary results indicate an increase in both teacher and student engagement, fostering critical thinking skills from an early age. This initiative positively impacts students’ critical literacy abilities, equipping them to tackle future informational challenges effectively.